2010
DOI: 10.1080/13803391003645657
|View full text |Cite
|
Sign up to set email alerts
|

Influence of poor effort on self-reported symptoms and neurocognitive test performance following mild traumatic brain injury

Abstract: When considering a diagnosis of postconcussion syndrome, clinicians must systematically evaluate and eliminate the possible contribution of many differential diagnoses, comorbidities, and factors that may cause or maintain self-reported symptoms long after mild traumatic brain injury (MTBI). One potentially significant contributing factor is symptom exaggeration. The purpose of the study is to examine the influence of poor effort on self-reported symptoms (postconcussion symptoms and cognitive complaints) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 81 publications
5
42
0
Order By: Relevance
“…52 In adults after mTBI, ∼50% of the variance in neuropsychological abilitybased test performance is accounted for by whether examinees exert adequate effort as measured by PVTs. [53][54][55][56] We found that nearly 40% of the abilitybased variance was accounted for by PVT performance in children after mTBI, 57 supporting the idea that some of the cognitive effects that are attributed to pediatric mTBI in clinical and research contexts are likely better explained by noncredible effort.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…52 In adults after mTBI, ∼50% of the variance in neuropsychological abilitybased test performance is accounted for by whether examinees exert adequate effort as measured by PVTs. [53][54][55][56] We found that nearly 40% of the abilitybased variance was accounted for by PVT performance in children after mTBI, 57 supporting the idea that some of the cognitive effects that are attributed to pediatric mTBI in clinical and research contexts are likely better explained by noncredible effort.…”
Section: Discussionmentioning
confidence: 69%
“…55,58,59 Even after controlling for other factors that influenced symptom reporting in this sample (eg, female gender, premorbid anxiety/depression, time since injury), MSVT performance remained a robust unique predictor of the level of endorsed symptomatology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a randomized controlled trial, early individual intervention by a qualified rehabilitation team didn't appear to improve the outcome of one year after injury among persons with MTBI-related fatigue (10), nor after 10 years (11). Moreover, some studies indicated that intervention focusing on post-concussion symptoms (PCS) might in fact increase the awareness of PCS-like symptoms among subjects exposed to such injuries (12). Currently, there remains a dearth of evidence regarding the appropriate management of subjects with long-term post-MTBI fatigue.…”
mentioning
confidence: 99%